Tender Loving Care: A Conceptual Analysis - Kumiko Kido; Akemi Mitani; Yuko Uemura (Women, Midwives and Midwifery, 2023)
Background: Studies have shown that combining tender loving care (TLC) with the treatment of patients with recurrent miscarriages can improve pregnancy outcomes. The importance of TLC has long been recognised in studies on psychiatric, gerontological, and end-of-life nursing in Western countries. Recently, randomised controlled trials (RCTs) have been used to examine the improvement in outcomes with the addition of TLC to the treatment of patients with recurrent miscarriages; however, no conclusions have been reached. TLC is a highly beneficial and harmless intervention that is not necessary for conducting RCTs. Therefore, healthcare professionals need to be aware of exercising TLC when treating patients with recurrent miscarriages. However, the concept of TLC is ambiguous and its definition is unclear.